Current Status of Adverse Drug Reaction Reporting by the Physicians in A Medical College Hospital (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: In order to improve the spontaneous Adverse Drug Reaction (ADR) reporting practice by the physicians, there is an obligatory need to investigate the current situation of ADR reporting by them. The study was conducted to observe the ADR reporting pattern among physicians in a tertiary medical college hospital.Materials and methods: This was a descriptive cross sectional study carried out in a tertiary medical college hospital during the study period of March 2020 to October 2020. Data were collected from 100 physicians working on different departments using self designed pretested questionnaire by convenient sampling technique.Results: Among the 100 respondents 70 provided response to questionnaire giving a response rate 70%. Most of the respondents (61.43%) had adequate knowledge on ADR reporting. A good number of respondents showed positive attitude but there is no practice of ADR reporting though most of the respondents (84.3%) had experienced it in last 1 year. Most of the respondents experienced ADR with antibiotic (81.35%), NSAIDs (33.89%) & anticonvulsants (15.25%) and maximum (44.06%) experienced ADR was with skin, 30.50% with GIT and 23.03% with respiratory system involvement. The cause of under reporting was mainly due to inaccessible ADR form, busy schedule, unaware of how and whom to report and lack of motivation to report. The respondents would be encouraged to report ADR if they were provided with simple & available reporting form, regular guideline & bulletin.Conclusion: There is an urgent need for educational training & seminar regarding our national online reporting system to emphasizing ADR reporting.Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 8-13